ACUMAAF: ambiente de computação ubíqua para o monitoramento e avaliação de atividade física - Nunes, Douglas Fabiano de Sousa (2012)
The physical inactivity has been indicated by the World Health Organization (WHO) as one of the main risk factors for the incidence of Chronic Non-Communicable Diseases (CNCDs). Millions of deaths in the world are a result of these diseases, and this number has increased each year. In an attempt to change this scenario WHO has stimulated regular practice of physical activities, because they play an important role in preventing CNCDs. In Brazil, these activities are performed by health units which generate a large amount of data that need treatment. To deal with this problem we developed UCEMEPA, an environment that employs Ubiquitous Computing technologies and wireless communication networks, in order to monitor remotely and evaluate participants of physical activity groups in real-time. This environment automatically collects physiologic data, and provides indicators which will support and direct public policies for promoting physical activity. In this sense, UCEMEPA will contribute for the promotion of health and quality of life, and for the conduction of longitudinal studies aiming to establish correlations between the practice of physical activity and CNCDs prevention.